Knowledge, Attitude, and Compliance in Taking Blood Supplement Tablets (TTD) and The Incidence of Anemia in Adolescent Girls - Yana Listyawardhani; Muhamad Zulfikar Mansyur (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Anemia in adolescent girls remains a prevalent health problem and has the potential to impact the quality of future health. Anemia prevention is influenced not only by knowledge, but also by attitude and compliance in consuming iron supplement tablets (TTD). This study aimed to analyze the relationship between knowledge and attitude regarding anemia, as well as compliance with TTD consumption, and the incidence of anemia in adolescent girls. This study utilized an observational design with a cross-sectional approach. The sample consisted of 86 female students at SMP Negeri 5 Tasikmalaya City, selected using the proportional stratified random sampling technique. Data were collected using questionnaires, TTD consumption checklist sheets, and hemoglobin level measurements using the HemoCue 201+ device, and were analyzed bivariately using the Chi-square test. The results showed that most subjects had low knowledge (62.8%) and were non-compliant in consuming TTD (55.8%), with an anemia incidence of 48.8%. There was a significant relationship between knowledge and attitude (p = 0.024) as well as the incidence of anemia (p = 0.049). Additionally, a relationship was found between attitude and the incidence of anemia (p = 0.018), as well as between compliance with TTD consumption and the incidence of anemia (p = 0.028). It can be concluded that attitude and compliance with TTD consumption play a more direct role in the incidence of anemia compared to knowledge. Therefore, interventions need to be directed not only toward increasing knowledge, but also toward shaping the attitude and behavior of adolescents.